Manajemen Pelatihan Dakwah Untuk Meningkatkan Kualitas Dakwah Sholawat Wahidiyah Di Dewan Pimpinan Pusat Penyiar Sholawat Wahidiyah Ngoro Jombang Tahun 2022 - Fahmi, Moh Ifan; Attatmimi, Achmad Habib (Ats-Tsaqofi: Jurnal Pendidikan dan Manajemen Islam, 2022)
This study aims to determine the planning, implementation and evaluation of da'wah training in improving the quality of sholawat wahidiyah da'wah in the Central Executive Board of Sholawat Wahidiyah Broadcasters Ngoro Jombang. The method used in this research is qualitative method. The subject of the research is everything related to the training activities of sholawat Wahidiyah Ngoro Jombang. Our data sources were obtained from the chairperson, deputy, secretary II of the Central Executive Board Assistant and the first chairman of the implementation of the caderization of da'i Wahidiyah as well as participants in the training of sholawat Wahidiyah. Data collection techniques using observation, documentation and interviews. The data analysis technique used a qualitative descriptive analysis technique. For the validity of the data using triangulation technique. The results of this study reveal that a series of da'wah training management processes, namely (1) Planning includes identifying the needs of training participants, determining training objectives, preparing training materials, selecting training participants, and scheduling training implementation times. (2) The Implementation includes: observing the appropriate training materials based on the abilities of the trainees, determining the training method, namely the marketing method (ice breaker) and brainstorming method, providing the facilities needed in the implementation of the da'wah training. (3) Evaluation of da'wah training in improving the quality of sholawat wahidiyah da'wah in the Central Executive Board of Wahidiyah sholawat broadcasters.